2014
DOI: 10.1002/esp.3643
|View full text |Cite
|
Sign up to set email alerts
|

Considering river structure and stability in the light of evolution: feedbacks between riparian vegetation and hydrogeomorphology

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 165 publications
(388 reference statements)
1
75
0
4
Order By: Relevance
“…Alternatively, another interpretation of the guild‐by‐environment interactions found here is that the use of guilds obscures significant variation in species‐specific response–effect relationships. While the argument can be made that response–effect linkages are likely to be strong in riparian plant communities (Corenblit et al, ; Diehl et al, ), these linkages may be disrupted in environments with artificial flow regimes. Species within each of the effect guilds in this system do differ substantially in their responses to hydrology and climate (Butterfield, Palmquist, & Ralston, ), which may support a more individualistic approach to assessing response–effect relationships with respect to biotic feedbacks on sand deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, another interpretation of the guild‐by‐environment interactions found here is that the use of guilds obscures significant variation in species‐specific response–effect relationships. While the argument can be made that response–effect linkages are likely to be strong in riparian plant communities (Corenblit et al, ; Diehl et al, ), these linkages may be disrupted in environments with artificial flow regimes. Species within each of the effect guilds in this system do differ substantially in their responses to hydrology and climate (Butterfield, Palmquist, & Ralston, ), which may support a more individualistic approach to assessing response–effect relationships with respect to biotic feedbacks on sand deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Plant traits and feedbacks on sedimentation may indeed reflect adaptive responses to the flow regime (Corenblit, Davies, Steiger, Gibling, & Bornette, ; Lytle & Poff, ), but river regulation can introduce new selection pressures on vegetation and sediment dynamics that differ from expectations based on long‐term evolutionary processes (Bejarano, Nilsson, & Aguiar, ; Merritt & Cooper, ). A common downstream consequence of dams is reduced seasonal flood magnitude, as well as a change in the timing of flooding (Petts, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fluvially disturbed systems, self‐organization processes are accentuated by interactions between plants, the land surface and flowing water and sediment (Francis et al ., ; D'Odorico et al ., ; Corenblit et al ., ) giving rise to questions regarding the degree to which patterns emerge or are imposed by physical conditions or processes and other ecological factors (Scheffer et al, 2013). In general, local vegetated areas with relatively high above‐ground biomass (e.g.…”
Section: A Conceptual Model Of Vegetation–hydromorphology Interactionmentioning
confidence: 99%
“…The combination of local and downstream or downwind protective–accretive and off‐site erosive effects of plants controls spatial and temporal self‐organization of BEs, mainly during the biogeomorphic phase (Temmerman et al ., ; Bouma et al ., , ; Kim, ; Corenblit et al ., ). It has been further suggested that the pattern of sediment trapping and erosion corresponds to a biogeomorphic scale‐dependent feedback.…”
Section: Criterion 2: Effect Traits Of Engineer Plants That Modulate mentioning
confidence: 99%